Psicologia positiva e envelhecimento : propriedades psicométricas da escala de gratidão para idosos brasileiros (G20 IB) - Viana, Susy Ane Ribeiro (2021)
Aging is a natural factor in human development. However, the increase in life expectancy, particularly in developing countries, has generated several economic, political and social concerns. Among them, we can point out health and quality of life throughout aging. Positive psychology shows as ingredients for happiness, the development of strengths and virtues present in all individuals, including gratitude. Several studies demonstrate that gratitude is an important construct in promoting health and subjective well-being. Several assessment instruments have been translated and adapted to the Brazilian context, but there are still few that contemplate the elderly population. The Gratitude Scale for Elderly Brazilians (G20-IB) was translated and adapted in order to fill this gap in the psychological assessment. It is an instrument that evaluates gratitude in four different facets: Interpersonal Gratitude (IG), Gratitude in the face of Suffering (GS), Expression of Gratitude (EG) and, finally, Recognition of Gifts (RD). As it encompasses emotional, cognitive, existential and behavioral aspects of gratitude, it was decided to choose it in this study. This study aims to present the psychometric properties of the Gratitude Scale for Elderly Brazilians (G20-IB) through validation analysis. To achieve this objective, two empirical articles were prepared. The first article had the main objective of translating and culturally adapting the Gratitud Cuestionário de 20 items (G20) to Brazilian Portuguese. The second article aimed to present evidence of validity of the scale adapted to the elderly, G20-IB. The method was organized in two stages: article 1) Translation and cross-cultural adaptation of the G20; and in article 2) Psychometric analysis of the G20 IB. In the first article, 93 individuals participated, divided into: 3 Spanish-Portuguese translators, 3 Portuguese-Spanish translators, 2 expert judges with extensive experience in the field of psychological assessment, 10 non-expert judges and 73 elderly. In the second article there were 156 elderly participants, recruited for convenience, from Amazonas, Santa Catarina and Rio Grande do Sul. The research battery contained the G20-IB, the sociodemographic characterization questionnaire, Geriatric Depression Scale (GDS-15). Positive Affects and Negative Affections Scale (PANAS), Mini Mental State Examination (MMSE). For the psychometric analysis, analyzes of convergent validity, discriminant validity, construct validity and reliability were performed. All participants, in both studies, read and signed the Free and Informed Consent Form (ICF). This research was submitted to evaluation and approved by the PPG Scientific Commission on Biomedical Gerontology and by the Research Ethics Committee, both from PUCRS (CAAE 49727115.0.0000.5336). The results of article 1 showed that the G20 obtained an agreement index of K equal to 1 (one), indicating 100% agreement. In Cronbach's Alpha test, it showed an alpha of 0.817 of the total scale in its internal consistency and the reliability remained between 0.818 and 0.797. In article 2, the results indicated that the structure of the G20 IB was built divided into four aspects (GI, GS, RD, EG) that are significantly related to each other and to the scale as a whole. The internal consistency of the scale, measured by Cronbach's alpha coefficient (αC), the estimate was satisfactory, reaching 0.934. There was evidence of discriminating validity of the gratitude scale, compared to the MEEN and GDS tests. It is concluded that the G20 and G20 IB scales are adequate and applicable tools for measuring gratitude in different contexts and for different populations. The results showed that the scales are suitable for use in the Brazilian population, as their internal consistency and reliability were satisfactory. In the second article, we found that the validation of the G20-IB may contribute to gerontology, providing material to supply the demand for instruments of Positive Psychology that are adapted to the elderly, thus being able to collaborate for the elaboration of new intervention studies and clinical practice to promote health and well-being for this population. New studies are still needed, which may include variables that were limited in this thesis.